Retinometry : a Literature Review - Febrina Art; Ramzi Amin; AK Ansyori (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2018)
Sharp vision is a major concern in cataract cases. Sharp improvement in vision is the expected outcome of the management of cataract cases, namely by operative measures. Before surgery, there are several ophthalmological examinations that must be performed. Quantitative instruments have been developed to determine the visual potential of eyes that experience turbidity of refractive media. One examination that can be done is a retinometry examination that is the examination of the sharp potential of vision with a retinometer. Retinometry is a process of measuring sharp eyes using a retinometer to determine the potential for sharp eyesight. Retinometer is one tool that uses the principle of interference fringes to assess the patient's sharp vision through a cloudy lens. On a retinometer, a light source is split into two rays which then enter the least turbid lens area so that interference grating is formed on the retina. The lattice can have a vertical, horizontal or oblique meridian orientation